IMPROVED FMCW RADAR SYSTEM FOR MULTI-TARGET DETECTION OF HUMAN RESPIRATION VITAL SIGN - Pratiwi, Hana; Hidayat, Mujib R.; Pramudita, A. A.; Suratman, Fiky Y. (Indonesian Institute of Sciences, 2019)
Frequency Modulated Continuous Wave (FMCW) radar system has been developed and applied for various needs. Based on the conventional FMCW radar concept, a large bandwidth is needed to detect small displacements in the chest wall or abdomen related with respiratory activity. To overcome the need for large bandwidths in detecting vital respiratory signs, several improvements to the FMCW system are proposed in this paper. The phase-detection concept has been elaborated in improving the capability of FMCW to detect the small displacement. In developing multi-target detection capability, range detection capability through beat frequency output needs to be combined with the phase-detection method. Theoretical and simulation studies were performed to investigate the concept of combining range detection and phase detection for detecting respiration on multi-target. The results show that the proposed method is well-performed in detecting the multi-target respiration in high noise reflection.